EFFECT OF PROCESSING PARAMETERS ON THE MECHANICAL-PROPERTIES OF CARBONIZED PHENOLIC RESIN - CHOE, CR; LEE, KH; Yoon, Byung Il (PERGAMON-ELSEVIER SCIENCE LTD, 1992)
Phenolic resin is carbonized in flowing helium up to 1100-degrees-C. The mechanical properties of carbonized products are closely related to the microstructure formed during carbonization. The microstructure of carbonized products is very porous. This porous structure is determined by the rate of gas evolution and the rate of diffusion of evolved gases, which are dependent on heating rate and sample dimension. At lower heating rates, the pore structure is uniform and mainly consists of narrow pores with small radius. With increasing heating rates, the mechanism of pore formation changes significantly. When the heating rate is greater than a critical level, some of the evolved gases create irregular pores and diffuse explosively from the bulk. Therefore, if the heating rate is over a critical level, the flexural modulus of carbonized products suddenly drops due to irregular pore formation in the bulk. The critical heating rate is highly affected by the sample dimension and falls off exponentially with increasing sample thickness.